2018
DOI: 10.2147/opth.s160110
|View full text |Cite
|
Sign up to set email alerts
|

Color vision deficiency among biomedical students: a cross-sectional study

Abstract: PurposeTo determine the prevalence of color vision deficiency (CVD) among first-cycle students of the Faculty of Medicine and Biomedical Sciences of the University of Yaoundé I.Patients and methodsA cross-sectional descriptive study was carried out between October 1, 2015 and May 31, 2016. Distant visual acuity was measured and color vision test done for all consenting students. Ishihara’s plates were used to test all the participants. Those who failed the test were tested with the Roth’s 28 Hue test for confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 11 publications
(20 reference statements)
3
15
0
Order By: Relevance
“…Colour vision deficiency (CVD) or colour blindness, is the inability or decreased ability to distinguish different colours under normal lighting conditions [ 1 ]. It is one of the commonest disorders of vision [ 2 ] and the incidence of CVD varies from race to race and different in different geographical area [ 3 , 4 ]. However, most of colour blind cases remain undetected due to absence of proper screening [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Colour vision deficiency (CVD) or colour blindness, is the inability or decreased ability to distinguish different colours under normal lighting conditions [ 1 ]. It is one of the commonest disorders of vision [ 2 ] and the incidence of CVD varies from race to race and different in different geographical area [ 3 , 4 ]. However, most of colour blind cases remain undetected due to absence of proper screening [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In all classes of severity, males had a higher preponderance. In the Deutan group, about 24% (24) where of the mild and moderate severity while 7% (7) had severe Deutan patterns.…”
Section: Severity Of Color Blindness Between Gendersmentioning
confidence: 97%
“…The prevalence of colour vision deficiency is expected to increase globally with the growing population, and varies among different races and geographical areas [2–4]. It has been reported that most people with colour vision defects remain undiagnosed [3, 4]. Colour vision deficiency is therefore under-reported due to a lack of its awareness and the absence of proper screening to detect this in the general population [4, 5].…”
Section: Introductionmentioning
confidence: 99%